A new care paradigm in geriatric head and neck surgical oncology. Issue 3 (27th June 2013) - Shuman, Andrew G.; Korc‐Grodzicki, Beatriz; Shklar, Victoria; Palmer, Frank; Shah, Jatin P.; Patel, Snehal G.
Abstract Background and Objectives Perioperative management of elderly patients with head and neck cancer poses unique challenges. Our objective is to describe the implementation and feasibility of a novel intervention designed to improve perioperative care in geriatric head and neck surgery. Methods This pilot study was performed in a single‐institution, NCI‐designated comprehensive cancer center. All surgical patients with head and neck cancer over age 75 were offered perioperative consultation with fellowship‐trained geriatricians focusing in geriatric oncology. Results Between 2010 and 2011, a total of 168 patients requiring head and neck surgery were seen by the geriatric service, of which 94% subsequently underwent surgery. Apart from preoperative medical optimization, geriatricians assisted in complex decision‐making regarding the indications for cancer‐directed therapy. Postoperatively, they assisted in preventing and treating delirium and poly‐pharmacy, facilitating discharge planning, and initiating rehabilitation. Postoperatively, 87% were discharged home, and 13% required placement in skilled nursing facilities. At 24 months, overall survival was 80%. Patients, surgeons and geriatricians alike were enthusiastic about the initiative, which is expanding within the institution. Conclusion Geriatric perioperative support for elderly head and neck cancer patients is well‐received with promising potential. The tangible impact and direct benefits of this pilot initiative require additional study. J. Surg. Oncol. 2013; 108:187–191. © 2013 Wiley Periodicals, Inc.